STRUKTUR NARATIF DALAM NOVEL CINTA TAK PERNAH TEPAT WAKTU KARYA PUTHUT EA (KAJIAN NARATOLOGI MIEKE BAL) - Nur Asyikin; Muhammad Rapi Tang; Sultan Sultan (20-87-2496)
The Narrative Structure in the Novel Cinta Is Never On Time by Puthut EA. This study aims to reveal the narrative structure contained in the novel Cinta Tak Never timely by Puthut EA based on Mieke Bal's narrative review. The type of research used is qualitative research. Data was collected by sorting out quotes in Puthut EA's Cinta Is Never On Time novel which contains a narrator, focalizer and fabula. The results of this study indicate that the narrator and focalizer are played by the character “I” in the story. Fabula has an important role in shaping the series of stories and plots in the novel being analyzed. Fabula which consists of events and the location of the events, as well as actors. Events and locations are combined in the analysis, so that the storyline can be arranged based on logical and chronological elements, namely arranged systematically (sequentially) starting from the mother's anxiety then meeting with several girls, the main character experiencing severe stress to healing and acceptance of himself.